Analisis Pemahaman Guru Terkait Karater Entrepreneur Anak Usia Dini - Ajang Ramdani (Al-Marifah | Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this study is to obtain an in-depth picture of the teacher's understanding ofthe entrepreneurial character in early childhood education. This research is motivated bythe emergence of social and cultural views that children are seen as less competent insolving problems and making decisions in their own environment. In fact, children have astrong curiosity about everything around them and have an entrepreneurial spirit. The datacollection technique is done through interviews. The subjects in this study were ECEteachers in the City and District of Tasikmalaya. The data analysis used is qualitative dataanalysis with thematic techniques. The results showed that the teacher's understanding ofthe entrepreneurial character can be described through the teacher's perception ofentrepreneurial learning, the level of importance/urgency of entrepreneurship learningaccording to the teacher, the implementation of entrepreneurial learning andentrepreneurial learning activities that have been carried out in their respectiveinstitutions. Thus, there is a need for policies that can facilitate and help teachers todevelop professionalism, especially in entrepreneurial learning. So that entrepreneuriallearning can be structured holistically as an integrated learning in the ECE curriculu